Preaching the just word - Burghardt, Walter J. (New Haven : Yale University Press, 1996)
"In this inspiring and compassionate book, one of America's foremost Catholic theologians discusses why we must apply biblical justice - and not merely ethical/legal justice - to matters concerning the poor, the oppressed, and the marginalized. Focusing on abused or neglected children, the AIDS-afflicted, the elderly, women, African-Americans, refugees, and prisoners on death row, Father Walter Burghardt urges that we become sensitive to their problems and faithful to the responsibilities we have undertaken in our covenant with God. We must hear the cries of the poor, he says, because social doctrine should evolve in large measure from the needs of people who share more of Jesus' crucifixion than his resurrection."--Jacket
Includes bibliographical references (pages 121-141) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Catholic Church -- Doctrines; Église catholique -- Doctrines; Catholic Church; Christianity and justice -- Catholic Church; Catholic preaching; Prédication -- Église catholique; RELIGION -- Christianity -- General; RELIGION -- Christian Life -- Social Issues; RELIGION -- General; Catholic preaching; Christianity and justice -- Catholic Church; Theology, Doctrinal